2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7318467
|View full text |Cite
|
Sign up to set email alerts
|

Voice pathology classification based on High-Speed Videoendoscopy

Abstract: This work presents a method for automatical and objective classification of patients with healthy and pathological vocal fold vibration impairments using High-Speed Videoendoscopy of the larynx. We used an image segmentation and extraction of a novel set of numerical parameters describing the spatio-temporal dynamics of vocal folds to classification according to the normal and pathological cases and achieved 73,3% cross-validation classification accuracy. This approach is promising to develop an automatic diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Others have used classifications based on a combination of the vocal fold shape and vascular pattern [34]. It has also been attempted to correlate voice pathologies with endoscopic videos of the vocal fold [23]. Furthermore, high-speed videos are analyzed with wavelet-based phonovibrograms and it is shown that a distinction between malignant and precancerous vocal fold lesions is possible [35].…”
Section: Related Workmentioning
confidence: 99%
“…Others have used classifications based on a combination of the vocal fold shape and vascular pattern [34]. It has also been attempted to correlate voice pathologies with endoscopic videos of the vocal fold [23]. Furthermore, high-speed videos are analyzed with wavelet-based phonovibrograms and it is shown that a distinction between malignant and precancerous vocal fold lesions is possible [35].…”
Section: Related Workmentioning
confidence: 99%
“…The left and right sides were determined automatically by fitting an ellipse on the segmented glottal area and assigning its major axis length as the midline of the glottal area (Panek et al, 2015). As can be observed in Figure 6, the glottal area technique is inappropriate for identifying paralysis of the vocal cords.…”
Section: Resultsmentioning
confidence: 99%
“…A number of approaches have been developed to quantify vocal cord motion such as Glottal Area Waveform or GAW (Panek et al, 2015;Woo, 2014;Gonzalez et al, 2013), phonovibrography (Lohscheller et al, 2008), kymography (Švec & Schutte, 2012), glottography (Karakozoglou et al, 2012), spatiotemporal analysis (Zhang et al, 2007) etc. Most of the research studies have focussed on quantitative assessment of vocal cord vibration during voice production.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent work addressing these limitation using methods of machine learning, feature extraction, and automated analysis of HSV recordings have recently been shown to distinguish laryngeal pathologies with great accuracy. [35][36][37] Thus, it is likely that HSV imaging with automated multifeature objective analysis will become the standard method by which clinical laryngeal imaging and analysis will be conducted in the evaluation of voice disorders during the upcoming decade.…”
Section: High-speed Video Imagingmentioning
confidence: 99%